2008
DOI: 10.1292/jvms.70.743
|View full text |Cite
|
Sign up to set email alerts
|

A PCR-Based Epidemiological Survey of Hepatozoon canis in Dogs in Nigeria

Abstract: ABSTRACT. The prevalence of Hepatozoon canis infections in dogs in Nigeria was surveyed using molecular methods. DNA was extracted from blood samples obtained from 400 dogs. A primer set that amplified the Babesia canis 18S rRNA gene, which has high similarity to the H. canis 18S rRNA gene, was used for the PCR. As a result, samples from 81 dogs (20.3%) produced 757 bp bands, which differed from the 698 bp band that corresponded to B. canis infection. The sequence of the PCR products of 10 samples were determi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

3
9
0
1

Year Published

2009
2009
2019
2019

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 19 publications
(13 citation statements)
references
References 12 publications
(23 reference statements)
3
9
0
1
Order By: Relevance
“…(JEFFERIES et al, 2003), showed a band that was about 500 bp greater than the Babesia band, and was also able to detect Hepatozoon species (O'DWYER et al, 2009). Similar results were obtained by Oyamada et al (2005) and Sasaki et al (2008).…”
Section: Molecular Diagnosissupporting
confidence: 78%
“…(JEFFERIES et al, 2003), showed a band that was about 500 bp greater than the Babesia band, and was also able to detect Hepatozoon species (O'DWYER et al, 2009). Similar results were obtained by Oyamada et al (2005) and Sasaki et al (2008).…”
Section: Molecular Diagnosissupporting
confidence: 78%
“…In the present study, cytological analysis of the blood samples yielded negative results for H. canis infection, which was similar to that reported by Sasaki et al (2008), who did not detected H. canis gamonts in the blood smears of 400 dogs. Absence of H. canis gamonts in the blood smears may be because of the low sensitivity of the technique and/or because of low or intermittent parasitemia in the dogs in this region (Baneth et al, 1998).…”
Section: Discussionsupporting
confidence: 92%
“…When compared with the results of other studies conducted in Turkey, the prevalence of canine hepatozoonosis was lower in this region than that of Aegean coast and south-eastern regions (Karagenc et al, 2006;Aktas et al, 2013). Higher infection rates were recorded to be as 25.8% by Karagenc et al (2006) in Turkey, 20.3% by Sasaki et al (2008) in Nigeria, 57.8% by Otranto et al (2011) in Italy, 11.4% by Jittapalapong et al (2006) in Thailand, 11.8% by Vojta et al (2009) in Croatia and 79.2% by de Miranda et al (2014) in Brazil. The lower infection rate of H. canis in this study might be attributed to the main vectors, but the studies related with the identification or distribution of the arthropod vectors of H. canis have not been organized in the region yet.…”
Section: Discussionmentioning
confidence: 51%